Demonstration of A-currents in pancreatic islet cells. - Smith, P; Bokvist, K; Rorsman, P (1989)
Voltage-activated K+ currents resistant to TEA but blockable by 4-AP were recorded from mouse pancreatic islet cells. These currents first become observable during depolarizations to voltages more positive than -40 mV, reaching a peak amplitude of 120 +/- 34 pA at +6 mV (n = 4), display rapid turn on (tau = 3.3 +/- 1.1 ms at +6 mV) and inactivate completely within 250 ms (tau = 65 +/- 5 at +6 mV). The current is subject to steady-state inactivation. The midpoint (Vh) of the inactivation curve (h infinity) was observed at -72 +/- 2 mV. The properties of this current resemble those reported for the A-current in neurons.